Peran Divisi Trade Partnership pada Pelaksanaan E-Commerce di Bibli.com(PT. Global Digital Niaga) - Harianja, Ruth; Viendyasari, Mila (Jurnal Vokasi Indonesia, 2018)
The purpose of this study was to determine the role of division Trade Partnership in the implementation of blibli.com E-commerce and to know the strengths and weaknesses in the work process of the Division of Trade Partnership and to explain the application of the functions of Trade Partnership to the blibli.com E-commerce business. From the results of research that can be explained that the Division of Trade Partnership on blibli.com E-commerce provides many benefits to Blibli.com in the process of pricing and searching for merchants who have not joined Blibli.com. In terms of Pricing Analysts with Price Comparison system, they can greatly help Blibli.com in developing the good image of Blibli.com E-commerce, especially in terms of recording the lowest prices for each product sold. This research uses descriptive qualitative method, where the researcher will record, manage, present and interpret and analyze data to provide an overview of how the role of the Trade Partnership Division in the implementation of Blibli.com E-Commerece. This study found that the role of the division Trade Partnership in Blibli.com E-commerce gave many benefits to Blibli.com in the process of pricing and searching for merchants who have not joined Blibli.com. In terms of Pricing Analysts who have a Price Comparison system, they can greatly help Blibli.com in developing the image of Blibli.com E-commerce, especially in terms of recording the lowest prices for each product sold.